2023
DOI: 10.3390/clockssleep5020025
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Comorbidities in Obstructive Sleep Apnea and the Pathophysiologic Mechanisms and Effects of CPAP

Victoria Sircu,
Silvia-Iaroslava Colesnic,
Serghei Covantsev
et al.

Abstract: Micro-arousals and the repeated desaturation of oxyhemoglobin, which are typical in obstructive sleep apnea syndrome (OSAS), have adverse effects on the health of patients, leading to a wide range of complications such as cardiovascular (arterial hypertension, pulmonary hypertension, chronic heart failure, arrhythmias, myocardial infarction), cerebrovascular (strokes), metabolic (insulin resistance, obesity, diabetes mellitus, metabolic syndrome), gastrointestinal (non-alcoholic liver disease), urinary (chroni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Untreated OSA is associated with major causes of morbidity and mortality, including hypertension, strokes, coronary artery disease, metabolic syndrome, cognitive impairment, and mood disorders [ 4 , 5 , 6 ]. The timely diagnosis and treatment of OSA may have a role in mitigating the development or progression of these comorbid conditions [ 7 ]. Positive airway pressure (PAP) therapy is the gold standard and most efficacious therapy for OSA [ 8 ], and is prescribed to 80% of those diagnosed with OSA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated OSA is associated with major causes of morbidity and mortality, including hypertension, strokes, coronary artery disease, metabolic syndrome, cognitive impairment, and mood disorders [ 4 , 5 , 6 ]. The timely diagnosis and treatment of OSA may have a role in mitigating the development or progression of these comorbid conditions [ 7 ]. Positive airway pressure (PAP) therapy is the gold standard and most efficacious therapy for OSA [ 8 ], and is prescribed to 80% of those diagnosed with OSA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with OSA may present with a variety of symptoms, including habitual snoring, fatigue, poor sleep quality, excessive daytime sleepiness (EDS), memory loss, headaches, and psychological disturbances ( 3 ). Many studies have confirmed that untreated OSA can damage multiple systems and organs and cause a variety of complications, including cardiovascular diseases, ischemic stroke, metabolic-related diseases, and neuropsychiatric complications ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Partial or complete obstruction of the upper airways during sleep, leading to episodes of apnoea or hypopnea, is the hallmark of the disease [5][6][7]. These events may result in metabolic changes, endothelial dysfunction, proinflammatory factor activation, and systemic oxidative stress, all of which raise the risk of cardiovascular disease [8][9][10][11][12]. In light of this, treatment is based on restoring physiological oxygen intake through continuous positive airway pressure (CPAP) therapy or surgical Biomedicines 2024, 12, 270 2 of 16 therapies addressing specific causative factors (i.e., maxillary expansion, maxillomandibular or jaw advancement surgery) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These events may result in metabolic changes, endothelial dysfunction, proinflammatory factor activation, and systemic oxidative stress, all of which raise the risk of cardiovascular disease [8][9][10][11][12]. In light of this, treatment is based on restoring physiological oxygen intake through continuous positive airway pressure (CPAP) therapy or surgical Biomedicines 2024, 12, 270 2 of 16 therapies addressing specific causative factors (i.e., maxillary expansion, maxillomandibular or jaw advancement surgery) [10,11]. The number of apnoeic or hypopneic occurrences per hour of sleep (apnoea-hypopnea index-AHI), is used to stratify the severity of OSAS into three categories-mild (5 ≤ AHI < 15), moderate (15 ≤ AHI < 30), and severe (AHI ≥ 30)-as determined in a polysomnography (PSG) sleep study [13], the standard diagnostic tool for OSAS.…”
Section: Introductionmentioning
confidence: 99%